Clinical outcomes of chronic heart failure patients with unsuppressed sleep apnea by positive airway pressure therapy - Naito, Ryo; Kasai, Takatoshi; Tomita, Yasuhiro; Kasagi, Satoshi; Narui, Koji; Momomura, Shin-Ichi (Frontiers in Cardiovascular Medicine, 2023)
Introduction Heart failure (HF) is an advanced stage of cardiac disease and is associated with a high rate of mortality. Previous studies have shown that sleep apnea (SA) is associated with a poor prognosis in HF patients. Beneficial effects of PAP therapy that is effective on reducing SA on cardiovascular events, were not yet established. However, a large-scale clinical trial reported that patients with central SA (CSA) which was not effectively suppressed by continuous positive airway pressure (CPAP) revealed poor prognosis. We hypothesize that unsuppressed SA by CPAP is associated with negative consequences in patients with HF and SA, including either obstructive SA (OSA) or CSA. Methods This was a retrospective observational study. Patients with stable HF, defined as left ventricular ejection fraction of ≤50%; New York Heart Association class ≥ II; and SA [apnea–hypopnea index (AHI) of ≥15/h on overnight polysomnography], treated with CPAP therapy for 1 month and performed sleep study with CPAP were enrolled. The patients were classified into two groups according to AHI on CPAP (suppressed group: residual AHI ≥ 15/h; and unsuppressed group: residual AHI < 15/h). The primary endpoint was a composite of all-cause death and hospitalization for HF. Results Overall, data of 111 patients including 27 patients with unsuppressed SA, were analyzed. The cumulative event-free survival rates were lower in the unsuppressed group during a period of 36.6 months. A multivariate Cox proportional hazard model showed that the unsuppressed group was associated with an increased risk for clinical outcomes (hazard ratio 2.30, 95% confidence interval 1.21–4.38, p = 0.011). Conclusion Our study suggested that in patients with HF and SA including either OSA or CSA, presence of unsuppressed SA even on CPAP was associated with worse prognosis as compared to those with suppressed SA by CPAP.